The splendor of the Church in Mary: Henri de Lubac, Vatican II, and Marian ressourcement - Nguyen, Theresa Marie Chau (The Catholic University of America Press, 2023)
"Henri de Lubac, SJ, (1896-1991) is one of the most renowned theologians of the twentieth century. Numerous studies have been undertaken to examine his many contributions to theology, but little attention has been paid to the specific topic of the relationship of the Blessed Virgin Mary and the Church in his writings. This was a topic that gave rise to contentious discussion at the Second Vatican Council, and although the Council fathers approved the integration of Marian doctrine into the Dogmatic Constitution on the Church, this synthesis of Mariology and ecclesiology has been largely neglected in theology today. The Splendor of the Church in Mary retrieves de Lubac's Marian ecclesiology and revives an understanding and appreciation of its enduring influence at the Vatican Council and beyond. The first part examines de Lubac's pre-conciliar works which evince a steady biblical and patristic ressourcement of Marian themes. It also explores his writings on Teilhard de Chardin's Eternal Feminine, Christian mysticism, and Amida Buddhism and discovers in them the essential building blocks of his Marian thought. The second part turns to the Second Vatican Council and post-conciliar developments. Rereading the debates and texts of Lumen Gentium through a Marian lens brings to light the extent of de Lubac's influence: Méditation sur l'Eglise (1953), his principal work on Mary and the Church, anticipated the structure and content of Lumen Gentium a decade before the Council. De Lubac's writings provided a theological compass for the Council fathers, and they continue to provide direction and orientation for ecclesiological discourse today. The Splendor of the Church in Mary culminates in a constructive analysis of one of the most pressing pastoral and ecclesiological questions of our times: the question of the relationship of the universal and particular churches. Directly engaging the crucial debate between then-Cardinal Ratzinger and Cardinal Kasper, it proposes that de Lubac's Mariology effectively offers a new perspective and a refreshing path forward. Attentive to the mystical identification of Mary and the Church, de Lubac's ressourcement has the potential to re-enchant and advance contemporary theology in new and significant ways"--